Both LmDicer-1 and two LmDicer-2s participate in siRNA-mediated RNAi pathway and contribute to high gene silencing efficiency in Locusta migratoria. (December 2022) - Gao, Lu; Wang, Yanli; Abbas, Mureed; Zhang, Tingting; Ma, Enbo; Merzendorfer, Hans; Zhu, Kun Yan; Zhang, Jianzhen
Abstract: Dicers belong to a class of large RNase III multidomain ribonucleases and are central components of the RNA interference (RNAi) pathways. In insects, Dicer-2 has been known to cleave long double-stranded RNA (dsRNA) in small interfering RNA (siRNA)-mediated-RNAi pathway. However, Dicer-1 is responsible for cleaving precursor microRNAs (pre28 miRNAs) in miRNA-mediated RNAi pathway. In this study, we identified one LmDicer-1 and two LmDicer-2 ( LmDicer-2a and LmDicer-2b ) genes in Locusta migratoria . The RNAi of RNAi assay showed that knockdown of each of the Dicer genes reduced RNAi efficiency against a target gene ( Lmβ-Tubulin ), suggesting that all these genes participated in the siRNA-mediated RNAi pathway. Sequence analyses of the siRNAs generated from ds Lmβ-Tubulin after silencing each LmDicer gene showed no significant difference in the pattern of siRNAs mapped to ds Lmβ-Tubulin . This result indicated that all the three LmDicers are capable of generating siRNAs from the dsRNA. We then generated recombinant proteins consisting of different domains using Escherichia coli expression system and incubated each recombinant protein with ds Lmβ-Tubulin. We found that the recombinant Dicer proteins successfully cleaved ds Lmβ-Tubulin . However, LmDicer-2a-R lacking dsRBD domain lost activity, suggesting that dsRBD domain is critical for Dicer function. Furthermore, overexpression of these proteins in Drosophila S2 cells improved RNAi efficiency. Our siRNA affinity chromatography and LC-MS/MS analysis identified LmDicer-2a, LmDicer-2b, LmR2D2, LmAgo2a, LmAgo1, LmStaufen and LmTARBP2 as constituents of RNA-induced silencing complex. Taken together, these data show that both LmDicer-1 and two LmDicer-2s all participate in siRNA-mediated RNAi pathway and likely contribute to high RNAi efficiency in L. migratoria . Graphical abstract: Image 1 Highlights: Biological roles of three Dicer genes in RNAi were characterized in the locust. All Dicers are capable of generating functional siRNA from dsRNA in vivo for RNAi. LmDicer-2a lacks dsRNA-binding domain but retains dsRNA cleavage activity in vivo . A dsRNA-binding protein may help LmDicer-2a bind to dsRNA for dicing activity. All three Dicers contribute to high RNAi efficiency of siRNA-mediated RNAi pathway.